Taxonomies on creativity - Tristán López, Agustín (2016)
This work presents a compendium of models and taxonomies classifying attributes involved in innovation and creativity. The frameworks proposed by several authors to characterize those processes, provide an approach to the subject and the means to its evaluation, both in qualitative and quantitative form. This work does not focus only on the psychological point of view of creative thinking, instead it considers its practical implications, following the proposals of researchers, developers and users in several knowledge fields, in various professions or academic environments.